Combined Administration of Metformin and Vitamin D: A Futuristic Approach for Management of Hyperglycemia - Tyagi, Sakshi; Mani, Shalini (Cardiovascular & Hematological Agents in Medicinal Chemistry, 2024)
Diabetes is a series of metabolic disorders that can be categorized into three types depending on different aspects associated with age at onset, intensity of insulin resistance, and beta- cell dysfunction: Type 1 and 2 Diabetes, and Gestational Diabetes Mellitus. Type 2 Diabetes Mellitus (T2DM) has recently been found to account for more than 85% of diabetic cases. The current review intends to raise awareness among clinicians/researchers that combining vitamin D3 with metformin may pave the way for better T2DM treatment and management. An extensive literature survey was performed to analyze vitamin D's role in regulating insulin secretion, their action on the target cells and thus maintaining the normal glucose level. On the other side, the anti-hyperglycemic effect of metformin as well as its detailed mechanism of action was also studied. Interestingly both compounds are known to exhibit the antioxidant effect too. Literature supporting the correlation between diabetic phenotypes and deficiency of vitamin D was also explored further. To thoroughly understand the common/overlapping pathways responsible for the antidiabetic as well as antioxidant nature of metformin and vitamin D3, we compared their antihyperglycemic and antioxidant activities. With this background, we are proposing the hypothesis that it would be of great interest if these two compounds could work in synergy to better manage the condition of T2DM and associated disorders.
Keywords: mitochondrion